Penerapan Doulingo Terhadap Peningkatan Hasil Belajar Siswa Pada Mata Pelajaran Bahasa Inggris di Kelas VII A SMP Negeri 4 Awangpone - Jusman Jusman; Sarmila Sarmila (Jurnal Ilmiah Wahana Pendidikan, 2023)
Application of Doulingo to Improving Student Learning Outcomes in English Subject in Class VII A of SMP Negeri 4 Awangpone, Thesis for the Education Technology Study Program, Faculty of Teaching and Education, University of Muhammadiyah Bone. Supervised by Advisor I Hj. Andi Kasmawati and Supervisor II Jusman. This research aims to determine the application of Doulingo to improving student learning outcomes in English subjects in class VII A of SMP Negeri 4 Awangpone. The type of research used is classroom action research. The data processed is the result of interviews with 1 (one) English teacher and 22 (twenty two) class VII A students. The data collection methods used in this research were observation, interviews and documents, where the author saw directly in the field. The results of the research obtained by the author are the application of Doulingo to improve student learning outcomes in English subjects in class VII A of SMP Negeri 4 Awangpone, which was obtained based on what was carried out in cycle I and cycle II. Data on the percentage increase in grades achieved by students when implementing the Duolingo application is quite important and can be said to be going well. Student input regarding the use of media is quite good. Students also become more active when practicing English through Duolingo. The application of the Duolingo application can improve student learning outcomes from the first cycle percentage data of 64.55 which is in the category below the completeness value of the KKM success criteria to increase from the second cycle percentage data which gets a percentage value of 80 which has achieved completeness of the success criteria exceeding the completeness of the KKM. This is because the results of action research have been achieved in cycle II and the implementation of the research has increased significantly, so this research does not need to be continued to the next cycle. Based on these results, the search stopped in Cycle II